2020
DOI: 10.3390/su12229372
|View full text |Cite
|
Sign up to set email alerts
|

Autogenous Shrinkage, Strength, and Hydration Heat of Ultra-High-Strength Paste Incorporating Nano-Zirconium Dioxide

Abstract: Ultra-high-strength paste (UHSP) combined with nanomaterials has been extensively studied. However, the research on nano-ZrO2 is limited. In this study, UHSP with various nano-ZrO2 contents is analyzed. The motivation of this study is to clarify the effects of nano-ZrO2 on the hydration products, strength, autogenous shrinkage, and hydration heat of UHSPs. The water-to-binder ratio (w/b) of the specimens is 0.2. The nano-ZrO2 content is 0, 1.5, and 3 wt.%. The strength is measured at the age of 3, 7, and 28 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
2
3
0
Order By: Relevance
“…Jensen et al [72] reported that at 28 days of curing, the AGS increased by as much as three times when cement is replaced with 10% silica fume at a water binder ratio of 0.3. Similar results were observed by Zhang et al [97].…”
Section: Supplementary Cementitious Materialssupporting
confidence: 92%
See 3 more Smart Citations
“…Jensen et al [72] reported that at 28 days of curing, the AGS increased by as much as three times when cement is replaced with 10% silica fume at a water binder ratio of 0.3. Similar results were observed by Zhang et al [97].…”
Section: Supplementary Cementitious Materialssupporting
confidence: 92%
“…Jensen et al [72] reported that at 28 days of curing, the AGS increased by as much as three times when cement is replaced with 10% silica fume at a water binder ratio of 0.3. Similar results were observed by Zhang et al [97]. Another study highlighted the effect of incorporating 5% and 10% of SF on the AGS of two different w/c ratios (0.26 and 0.35).…”
Section: Supplementary Cementitious Materialssupporting
confidence: 86%
See 2 more Smart Citations
“…The measurement of autogenous shrinkage was performed according to ASTM C1698 [30]. Since the internal relative humidity and internal temperature act as critical factors influencing the autogenous shrinkage of concrete [31], the autogenous shrinkage, internal relative humidity, and internal temperature of the AAS mortars were measured simultaneously in this study. We modified the ASTM C1698 measuring device by inserting a sensor in the center of the corrugated plastic tube to monitor the internal relative humidity and internal temperature.…”
Section: Autogenous Shrinkagementioning
confidence: 99%